2011
DOI: 10.1186/1750-1172-6-43
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive development in patients with Mucopolysaccharidosis type III (Sanfilippo syndrome)

Abstract: BackgroundMucopolysaccharidosis type III (MPS III, Sanfilippo syndrome) is a lysosomal storage disorder caused by a deficiency of one of the enzymes involved in the degradation of heparan sulfate.MPS III is characterized by progressive mental deterioration resulting in severe dementia. A number of potentially disease-modifying therapies are studied. As preservation of cognitive function is the ultimate goal of treatment, assessment of cognitive development will be essential in order to evaluate treatment effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
85
2
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 24 publications
(40 reference statements)
7
85
2
11
Order By: Relevance
“…Molecular study showed that the patient was homozygous for the mutation p.R245H. Our patient showed only mild manifestations of the disease; however, this mutation was previously reported in the severe phenotype of SS type A [Valstar et al, 2010[Valstar et al, , 2011.…”
contrasting
confidence: 48%
“…Molecular study showed that the patient was homozygous for the mutation p.R245H. Our patient showed only mild manifestations of the disease; however, this mutation was previously reported in the severe phenotype of SS type A [Valstar et al, 2010[Valstar et al, , 2011.…”
contrasting
confidence: 48%
“…Кроме того, по мнению многих исследователей, для достижения оптимального эффекта лечение должно быть начато на досимптомной стадии болезни, до начала необрати-мого повреждения ЦНС [10,16].…”
Section: гематоэнцефалический барьерunclassified
“…MPS-IIIB is characterized by delay in speech, mental retardation, hyperactivity, aggressive behavior, incapability in social interaction skills, aimless hand movements, inappropriate and limited eye contact, sleep disturbances, retardation in growth, and facial phenotypic features [3].…”
Section: Introductionmentioning
confidence: 99%
“…In these children, some features of psychiatric symptoms might be seen such as severe hyperactivity, uncontrolled impulsivity, temper tantrums, quasi-autistic patterns, and severe anxious mood [4]. These symptoms have changeable natures in which some of them might be lessened and some could increase and worsen [3]. Many studies related to this disorder demonstrated that patients with MPS-III have experienced sleep disorders, hyperactivity, aggressive behavior, inappropriate mood, temper tantrum and behavioral problems similar to this and there was a correlation between cognitive retardation and behavioral problems [5].…”
Section: Introductionmentioning
confidence: 99%